Time-optimal control of redundant manipulators - Galicki, Mirosław; Pająk, Grzegorz; Pająk, Iwona (Zielona Góra: Uniwersytet Zielonogórski)
A method of finding optimal controls for both non-redundant and redundant manipulators is considered. It is based on a strict convexifying of the original control set with any desired accuracy in the Hausdorff sense. The optimal controls thus obtained are shown to converge (weakly) to a bang-bang solution. Furthermore, this method produces also controls which may be directly used to provide nominal inputs in on-line manipulator control. A simple numerical example involving a three-degree-of-freedom revolute kinematically redundant manipulator is presented
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka